FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH - Yuni Subhi Isnaini; Sulpa Ida; Priscilla Jessica Pihahey (Nursing Arts, 2021)
Based on data at the Manokwari Regional General Hospital in 2018, there were 16 infant deaths with the cause of death namely 7 LBW, 5 people asphyxia, 4 RDS, while in 2019 the LBW incidence rate was 127 people and there was an increase in the infant mortality rate of 25 people. caused by 14 LBW souls, 7 RDS souls, 4 asphyxiated souls, this shows that the highest mortality is caused by LBW. Design This study uses a case-control research design, which is an analytical survey research that concerns how risk factors are studied using a retrospective approach. This research was conducted from May to June 2021. The number of samples in this study was 216 samples. The results of the Chi Square test for the maternal age factor obtained a p value of 0.601> 0.05, the results of the Chi Square test of the parity factor obtained a p value of 0.0021 < 0.005, the results of the Chi Square test for the gestational age factor obtained a p value of 0.000 < 0.005Keywords: LBW, maternal age, parity, gestational age